BrRLP48, Encoding a Receptor-Like Protein, Involved in Downy Mildew Resistance in Brassica rapa - Zhang, Bin; Li, Pan; Su, Tongbing; Li, Peirong; Xin, Xiaoyun; Wang, Weihong; Zhao, Xiuyun; Yu, Yangjun; Zhang, Deshuang; Yu, Shuancang; Zhang, Fenglan (Frontiers in Plant Science, 2018)
Downy mildew, caused by Hyaloperonospora parasitica, is a major disease of Brassica rapa that causes large economic losses in many Brassica rapa-growing regions of the world. The genotype used in this study was based on a double haploid (DH) population derived from a cross between the Chinese cabbage line BY and a European turnip line MM, susceptible and resistant to downy mildew, respectively. We initially located a locus Br-DM04 for downy mildew resistance in a region about 2.7 Mb on chromosome A04, which accounts for 22.3% of the phenotypic variation. Using a large F2 mapping population (1156 individuals) we further mapped Br-DM04 within a 160 kb region, containing 17 genes encoding proteins. Based on sequence annotations for these genes, four candidate genes related to disease resistance, BrLRR1, BrLRR2, BrRLP47 and BrRLP48 were identified. Overexpression of both BrRLP47 and BrRLP48 using a transient expression system significantly enhanced the downy mildew resistance of the susceptible line BY. But only the leaves infiltrated with RNAi construct of BrRLP48 could significantly reduce the disease resistance in resistant line MM. Furthermore, promoter sequence analysis showed that one salicylic acid (SA) and two jasmonic acid (JA)-responsive transcript elements were found in BrRLP48 from the resistant line, but no in the susceptible one. Real-time PCR analysis showed that the expression level of BrRLP48 was significantly induced by inoculation with downy mildew or SA treatment in the resistant line MM. Based on these findings, we concluded that BrRLP48 was involved in disease resistant response and the disease-inducible expression of BrRLP48 contributed to the downy mildew resistance. These findings led to a new understanding of the mechanisms of resistance and lay the foundation for marker-assisted selection to improve downy mildew resistance in Brassica rapa.